SIMS Lab Potsdam: Secondary Ion Mass Spectrometry Laboratory Potsdam - Michael Wiedenbeck; Alexander Rocholl; Robert Trumbull; Frédéric Couffignal (Journal of large-scale research facilities JLSRF, 2016)
Secondary Ion Mass Spectrometry (SIMS) is among the most powerful laboratory tools available to the analytical geochemist. Its strength lies in SIMS’ ability to produce high precision trace element and isotope ratio data on sample masses as small as 100 picograms. The Helmholtz-Centre Potsdam GFZ German Research Centre for Geosciences operates a fully equipped, large geometry SIMS instrument, which is supported by a comprehensive spectrum of peripheral instrumentation. This facility operates as an open user facility which supports the needs of the global geochemical community.